COST ACCOUNTING VIEW OF BSA STUDENTS AS FUTURE ENTREPRENEURS - Barana, Catherine Ann; Develos, Catherine Jean; Galamiton, Wella Jane; Vasquez, Michael B (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Cost accounting, a type of managerial accounting where the goal is to record the entire cost of production, provides fundamental business knowledge to make informed decisions about allocating resources, increasing output, and maximizing profit.  The exploration of cost accounting considering forecasting, budgeting, and planning is based on the views of the Bachelor of Science in Accountancy (BSA) students as future entrepreneurs. Utilizing a qualitative research methodology using the lens of phenomenology, three purposively selected fourth-year BSA students enrolled in the College of Business, Management, and Accountancy of Colegio de la Purisima Concepcion participated and provided data according to their lived experience. The research instrument used in this study was a validated semi-structured questionnaire with open-ended questions to generate comprehensive insights from the participants. The findings of the study highlight the relevance of the cost accounting to BSA students as future entrepreneurs. Cost accounting in consideration of forecasting, budgeting, and planning emerged three views that are contextual, procedural, and comparative in nature, hence, the CPC Views of Cost Accounting. The acronym CPC stands for Contextual view, Procedural view, and Comparative view. This study provides evidence that the cost accounting view helps students learn more about the financial implications of their decisions by utilizing cost accounting concepts, procedures, and methodologies. It may create reasonable financial objectives, allocate resources wisely, and make well-informed decisions under the light of the CPC views of Cost Accounting.